2013
DOI: 10.17660/actahortic.2013.979.48
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Bambara Groundnut, an Underutilised African Legume Crop as Part of the Bamlink Project - What Lessons Can We Learn?

Abstract: Bambara groundnut (Vigna subterranea L. Verdc.) is an underutilised, drought tolerant legume that has the potential to form an important part of Food Security for the coming decades. The challenges facing farmers to produce enough food for the growing world population -particularly that of climatic instability -are well documented and together represent probably one of the biggest challenges humanity has faced. Our extreme reliance on a limited number of staple (often nonindigenous and sometimes also poorly ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…In the last 30 years, drought breeding work on bambara groundnut has been limited and largely focused and elucidated by above ground shoot morpho-physiological studies [11,13,14,16,19,[36][37][38][39][40][41][42]. In order to fully understand and better manipulate the ability to tolerate water-limited conditions, the range of both above-and belowground variation present in bambara groundnut germplasm needs to be explored [43].…”
Section: Discussionmentioning
confidence: 99%
“…In the last 30 years, drought breeding work on bambara groundnut has been limited and largely focused and elucidated by above ground shoot morpho-physiological studies [11,13,14,16,19,[36][37][38][39][40][41][42]. In order to fully understand and better manipulate the ability to tolerate water-limited conditions, the range of both above-and belowground variation present in bambara groundnut germplasm needs to be explored [43].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically for Bambara groundnut, various molecular analyses of diversity have been reported to either argument or validate the various reports based on phenotypic descriptors (Table 6; Pasquet et al 1999;Massawe et al 2003aMassawe et al , 2002Olukolu et al 2012;Aliyu and Massawe 2013;Mayes et al 2013;Molosiwa et al 2015). The earliest report of diversity analysis at the molecular/cellular level in Bambara groundnut includes the report of Pasquet et al (1999).…”
Section: Overview Of Qualitative and Quantitative Phenotypic Diversitmentioning
confidence: 98%
“…(3) Based on the various reports indicating high allelic diversity, low observed heterozygosity and high inbreeding coefficient, a single landrace could be considered as an 'unselected cultivar/variety' (Molosiwa et al 2015). This could lead to 'short circuiting' of breeding with just few rounds of single seed/plant selection, enough to purify landraces for variety development (Mayes et al 2013;Aliyu et al 2015;Molosiwa et al 2015). This present an opportunity to explore various short to medium term strategies for variety development in breeding programmes ( Fig.…”
Section: Overview Of Qualitative and Quantitative Phenotypic Diversitmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the West-Central African genotypes and the South-Eastern African genotypes are always clustered separately throughout the molecular analysis [76]. In Bambara groundnut, studies on comparative genomics analysis between leaf transcriptome in Bambara groundnut and other crop species have been evaluated to enable the detection of suitable cross-species orthologues and the crop model genes [94,97,139]. The outcome revealed that soybean scored a similar maximum similarity transcript sequence to that of Bambara groundnut, and among the other species (Vigna radiate, Riciniscommunis, Populastrichocarpa, Arabidopsis lyrata, Vitisvinifera, and Medicagotruncatula) examined in the study and may be used in the form of a gene model in Bambara groundnut gene expression profiling [97].…”
Section: Research To Datementioning
confidence: 99%